The Limits of Cognitive Preferences: How Gender and Conceptual Understanding Shape Mathematical Representations - Nur Fauziyah; Septiana Maulidinah; Hasan Basri; Wannaporn Siripala (Jurnal Pendidikan MIPA, 2026)
This study aims to describe the profile of students' mathematical representations across visual, symbolic, and verbal aspects, and to examine visualist and verbalist cognitive styles from a gender perspective. A descriptive qualitative approach was used. Four students were purposively selected, consisting of male and female students with visualist and verbalist cognitive styles from a public high school. The instrument used was the Object-Spatial and Verbal Imagery Questionnaire (OSIVQ) to classify students into visualist and verbalist cognitive styles. Representation data were collected through a mathematical representation test focusing on function composition, and were supplemented by semi-structured interviews. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that visual representations by male and female visualist and verbalist students in solving mathematical problems were presented as images. In problems without image instructions, both male and female visualist students continued to use visual representations before switching to symbolic representations. There was no variation in the visual representations used by the subjects; the images used tended to be copied from their teachers. Male students, both visualists and verbalists, used symbolic representations less systematically than female students. In symbolic representation, visual students made errors at the algebraic operations stage, resulting in symbol errors, and vice versa. All subjects used verbal representation, but to a very small extent. Verbal representation was not used to explain the steps for completing the worksheet; it was only used to write the names of the concepts. Visual students, both male and female, tended to point to pictures when explaining the work process, whereas verbal students tended to point to symbols. Female visual and verbal students were more systematic in their explanations, while male visual and verbal students were less coherent. Keywords: mathematical representation, cognitive style, gender.